The optimisation of mm-Wave GaAs Gunn diodes using a parallel implementation of the Monte Carlo particle simulation technique - Van Zyl, Robert Ryk (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD) -- University of Stellenbosch, 2006.